Recent Progress in Interfacial Dipole Engineering for Perovskite Solar Cells - Ma, Yinyi; Gong, Jue; Zeng, Peng; Liu, Mingzhen (Nano-Micro Letters, 2023)
Design and modification of interfaces have been the main strategies in developing perovskite solar cells (PSCs). Among the interfacial treatments, dipole molecules have emerged as a practical approach to improve the efficiency and stability of PSCs due to their unique and versatile abilities to control the interfacial properties. Despite extensive applications in conventional semiconductors, working principles and design of interfacial dipoles in the performance/stability enhancement of PSCs are lacking an insightful elucidation. In this review, we first discuss the fundamental properties of electric dipoles and the specific roles of interfacial dipoles in PSCs. Then we systematically summarize the recent progress of dipole materials in several key interfaces to achieve efficient and stable PSCs. In addition to such discussions, we also dive into reliable analytical techniques to support the characterization of interfacial dipoles in PSCs. Finally, we highlight future directions and potential avenues for research in the development of dipolar materials through tailored molecular designs. Our review sheds light on the importance of continued efforts in this exciting emerging field, which holds great potential for the development of high-performance and stable PSCs as commercially demanded. Highlights: 1 The fundamental properties of electric dipoles and their specific roles in perovskite solar cells are discussed. 2 Research progress of interfacial dipoles in perovskite solar cells is summarized. 3 Challenges of deterministic characterization of electric dipoles and future perspectives are highlighted.